2001
DOI: 10.1128/aac.45.3.789-793.2001
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activities of the Novel Ketolide Telithromycin (HMR 3647) against Erythromycin-Resistant Streptococcus Species

Abstract: The in vitro susceptibilities of 184 erythromycin-resistant streptococci to a novel ketolide, telithromycin (HMR 3647), were tested. These clinical isolates included 111 Streptococcus pyogenes, 18 group C streptococcus, 18 group G streptococcus, and 37 Streptococcus pneumoniae strains. The MICs for all but eight S. pyogenes strains were <0.5 g/ml, indicating that telithromycin is active in vitro against erythromycin-resistant Streptococcus strains. All strains for which MICs were >1 g/ml had an erm(B) resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
69
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 27 publications
5
69
0
3
Order By: Relevance
“…Previous studies have demonstrated that telithromycin resistance in GAS is found exclusively in macrolide-resistant isolates expressing erm(B) (8,10,19). Consistent with this, we demonstrated the presence of erm(B) in two strains of GAS expressing the MLS i phenotype that were resistant to telithromycin.…”
supporting
confidence: 76%
“…Previous studies have demonstrated that telithromycin resistance in GAS is found exclusively in macrolide-resistant isolates expressing erm(B) (8,10,19). Consistent with this, we demonstrated the presence of erm(B) in two strains of GAS expressing the MLS i phenotype that were resistant to telithromycin.…”
supporting
confidence: 76%
“…Similarly, methylation of the tylosin contact site at G748 confers specific resistance to a subgroup of macrolides that are structurally related to tylosin (30). Telithromycin is the first ketolide to be approved for clinical use, and it has been demonstrated to be an effective antimicrobial agent (11,(24)(25)(26)(27). It is yet too soon to evaluate fully the extent to which resistance to telithromycin might develop in clinical isolates and whether this will involve mutation in domain II of the rRNA.…”
mentioning
confidence: 99%
“…Balfour et al, Bryskier y otros investigadores, han publicado que telitromicina es 2 a 5 veces más activa que claritromicina contra cocáceas gram positivas sensibles a eritromicina, tanto en Staphylococcus, S pneumoniae y S pyogenes 4,6 . Un hecho relevante es que telitromicina en S pneumoniae es activa independiente de su susceptibilidad a penicilina y eritromicina [21][22][23] . Nuestros resultados avalan esta observación, reflejada en una CIM 90 baja, independiente del resistotipo.…”
Section: Discussionunclassified
“…La CIM 90 de las cepas de SPNS y SPNI fue de 0,03 µg/ml y las cepas de SPNR presentaron una CIM 90 de 0,06 µg/ml. Todas las cepas de S pyogenes siguen siendo sensibles a penicilina, no así a macrólidos, en que hay cepas resistentes que se han asociado con el consumo del antibiótico [10][11][12]22,23 . Las cepas de S pyogenes estudiadas en esta serie, 100% fueron sensibles a telitromicina con CIM 50 de 0,015 µg/ml y CIM 90 de 0,5 µg/ml, a diferencia de la sensibilidad a eritromicina que fue de 89,5%, con rangos de CIM 50 y CIM 90 de 0,03 y 0,06 µg/ ml, respectivamente (Tabla 3).…”
Section: Discussionunclassified